A single NMT is relevant for Toxoplasma gondii lytic cycle - Alonso, A. M. (2018)
Toxoplasma gondii is the causative agent of toxoplasmosis. This disease affects almost one third of the world's population with devastating effects. Despite the significant progress that has been made in order to develop new compounds to treat toxoplasmosis, the current therapeutic agents frequently used have toxic side effects. As such, scientists are in real need of finding new targets of intervention. Protein myristoylation is a post- and co-translational modification that affects a variety of proteins in many cells including parasites. It is catalyzed by N-myristoyltranferase (NMT), a conserved enzyme that has been described to be essential in many protozoan pathogens. However, up to date, there is scarce information on NMT and the extent of this modification in T. gondii. In this work T. gondii NMT (TgNMT) was identified and characterized. Structural analyses suggest that there are differences between human and T. gondii NMTs, which could be of importance to design specific inhibitors. Furthermore, this protein presents NMT activity in vitro, is expressed in both intra- and extracellular parasites and interacts with predicted TgNMT substrates. Additionally, TgNMT activity seems to be important for the lytic cycle. An in silico myristoylome predicts 157 proteins to be targeted by this modification with some of them being critical for the life cycle of this parasite. This analysis suggests that myristoylation could be regulating calcium homeostasis which is critical for T. gondii pathogenesis. Together, these data indicate that TgNMT could be an interesting target of intervention for the treatment of toxoplasmosis.